SISTEM INFORMASI INVENTARIS PERALATAN LABORATORIUM BERBASIS WEB MENGGUNAKAN TEKNIK LABELLING QR CODE DI PT ITEC SOLUTION INDONESIA - Dony Kristiyanto; Dahlia Widhyaestoeti; Dewi Primasari (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
Itec Solution Indonesia is a company engaged in environmental consulting services, as a research service provider company PT. Itec Soluion Indonesia has three laboratories that are routinely used, namely chemistry, water and microbiology laboratories. In carrying out equipment inventory activities, the activity of recording all the tools in each laboratory still uses the manual method, namely by doing bookkeeping which is then entered into Microsoft Excel 2013. This method makes equipment data management not optimal because the work process takes a long time, especially when performing data searches and reporting. To solve this problem, it is necessary to implement a web-based inventory system designed using unified modeling language (UML) tools and built using the waterfall system development method and utilizing the Qr Code for labeling each device in the laboratory, with this system it can make it easier for officers to complete administration and documentation of the equipment of each device in the laboratory Keywords: Inventory, Qr Code, Waterfall, Information System.